2009
DOI: 10.1289/ehp.11654
|View full text |Cite
|
Sign up to set email alerts
|

Is There Evidence for Synergy Among Air Pollutants in Causing Health Effects?

Abstract: BackgroundEnvironmental air pollutants are inhaled as complex mixtures, but the long dominant focus of monitoring and research on individual pollutants has provided modest insight into pollutant interactions that may be important to health. Trends toward managing multiple pollutants to maximize aggregate health gains place increasing value on knowing whether the effects of combinations of pollutants are greater than the sum of the effects of individual pollutants (synergy).ObjectiveWe reviewed selected publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(102 citation statements)
references
References 31 publications
0
101
0
1
Order By: Relevance
“…Ozone and PM represent a common persistent problem in several cities, with important effects on public health (Craig et al, 2008). Although recent attention has been brought towards understanding the role of multipollutants interactions in air pollution related health effects (Mauderly and Samet, 2009), current methodological approaches have focused on ozone (Samoli et al, 2009) and, more importantly, in PM as the criteria pollutant with stronger associations with most of the described health effects.…”
Section: Health Studiesmentioning
confidence: 99%
“…Ozone and PM represent a common persistent problem in several cities, with important effects on public health (Craig et al, 2008). Although recent attention has been brought towards understanding the role of multipollutants interactions in air pollution related health effects (Mauderly and Samet, 2009), current methodological approaches have focused on ozone (Samoli et al, 2009) and, more importantly, in PM as the criteria pollutant with stronger associations with most of the described health effects.…”
Section: Health Studiesmentioning
confidence: 99%
“…For example, evidence for synergy among pollutants in causing health effects has been recently reviewed by Mauderly and Samet. 16 Several studies have confirmed that synergisms exist between O 3 and other pollutants in laboratory studies involving humans and animals. 17 Thus, the highly correlated nature of air pollution exposures and the potential for synergies raise questions about the adequacy of marginal, single-pollutant models.…”
Section: Introductionmentioning
confidence: 95%
“…To help advance understanding of the relationships between ambient air pollutant concentrations and asthma exacerbations in children, further characterization of the dose-response and pollutant lag effects are needed, as are investigations of pollutant species beyond the commonly measured urban air pollutants (3,7). Further investigation of pollutant mixtures and effect modification may also provide insights (8,9); for example, there have been reports of stronger pollution effects during the warm season (10-15) even though pediatric asthma rates peak during the cold season (16). To lessen concerns about uncontrolled confounding, aggressive control for variables, such as meteorology and seasonal asthma trends, is required.…”
mentioning
confidence: 99%